(untitled) (The Research of Medical Science Review, 2025)
Background: Mental health issues, including generalized anxiety, are increasingly recognized in athletes, with notable gender differences in prevalence and severity. This study aims to assess anxiety levels, psycho-social factors, and dietary intake among non-elite athletes, focusing on gender-based variations. Methodology: A total of 100 non-elite athletes (aged 17–29 years) from the University of Peshawar were selected using convenience and consent-based random sampling. Data was collected through a pretested questionnaire incorporating a validated Generalized Anxiety Disorder (GAD-7) scale for anxiety assessment. The analysis was conducted using SPSS software. ANOVA and Pearson Chi-Square tests were used to assess gender differences. Results: The results indicate that anxiety is prevalent among both male and female athletes, with mild anxiety being the most common level. Female athletes exhibited higher moderate anxiety (27.27%) compared to males (16.67%), while severe anxiety was more frequent in males (11.54%) than females (4.55%). Gender-based symptom analysis showed that females reported significantly higher nervousness (p = 0.038) and slightly higher excessive worrying, though most differences were not statistically significant. Overall, females tend to experience more moderate anxiety, whereas males are more likely to report severe anxiety symptoms. Conclusion: The findings highlight a greater burden of anxiety among female non-elite athletes, emphasizing the need for targeted mental health interventions. The study underscores the widespread impact of anxiety among athletes, revealing notable gender-based differences in severity. These results emphasize the necessity of tailored mental health support and intervention programs addressing the distinct psychological needs of both male and female athletes.